INNOVATION OF RESEARCH PERMIT SERVICES THROUGH THE NENI SI LINCA INFORMATION SYSTEM APPLICATION AT DPMPTSP SOUTH SULAWESI PROVINCE - Fitriyani, Fina; Sulmiah, Sulmiah; Sakawati, Herlina (Universitas Negeri Makassar, 2025)
The success of an innovation can be seen through the characteristics of an innovation. This study aims to determine the application of innovation in research permit services for the New normal innovation application of the online campus information system (Neni Si Linca). This research uses a qualitative approach with descriptive methods. The informants in this study consisted of 7 Neni Si Linca users, 5 employees and the head of DPMPTSP. The data collection techniques in this study were interviews, observations, and document reviews. Data validity checking in this study was carried out by triangulating sources. Data analysis techniques use data condensation, data presentation and conclusion drawing. The results of this study indicate that the application of the Neni SI Linca innovation can be seen from the suitability of innovation to the attributes or characteristics of innovation in this case the New normal innovation online campus information system (Neni Si Linca) at DPMPTSP South Sulawesi Province. There are five indicators on innovation attributes according to Roger (Suwarno, 2008), namely relative advantage, compability, complexity, triability, observability. Based on the results of observations and interviews, it shows that there are three successful indicators, namely relative advantage, compatibility (compability), trialability (triability) then there are 2 indicators that are not yet appropriate is complexity and observability